3313 "My research is their business, but I'm not their business": Patient and Oncologist Perspectives on the Commercialization of Research Data. (27th March 2019) - Spector-Bagdady, Kayte; Krenz, Chris; Gornick, Michele; Brummel, Collin; Kent, Madison; Chad Brenner, J.; Scott Roberts, J.; Shuman, Andrew G.
Abstract : OBJECTIVES/SPECIFIC AIMS: Our objective was to assess and compare the attitudes of patients with head and neck cancer and their clinicians regarding the commercialization of genetic research data. We explored whether such opinions changed when profits from such transactions were used to fund 1) cancer research, 2) academic research generally, or 3) if patients were given personalized genetic information in return. METHODS/STUDY POPULATION: This qualitative analysis was nested within a prospective precision oncology genomic sequencing study in an NCI-designated cancer center. We conducted paired, semi-structured interviews with enrolled participants with head & neck cancer and with their doctors (medical oncologists, surgical oncologists, and radiation oncologists). Interviews were recorded, transcribed, and coded for analysis. Codes were developed through an iterative process until saturation was reached, and all transcripts were double-coded (and discrepancies reconciled) to ensure reliability. RESULTS/ANTICIPATED RESULTS: We identified three main themes from the patients and clinicians: (1) Both clinicians and their patients were unclear about how the study protocol and informed consent form authorized patients' genetic data to be used and commercialized in the future. (2) Patients with cancer were generally more comfortable than their clinician thought they were regarding the ongoing research use of their genetic data and commercialization thereof. (3) There is a strong interest among patients and clinicians in focusing academic medical center profits from commercialization back into the research program from which the data was acquired, rather than being invested into academic research more broadly. DISCUSSION/SIGNIFICANCE OF IMPACT: Given patients' strong feelings about the commercialization of their data, our results highlight the need for greater transparency—both with patients and with their clinicians—about potential future use of research data. Clinicians appear inclined to be particularly cautious regarding access to and commercialization of patients' data, however patients generally hope that their data may be used to help future cancer patients. Explicit discussions with patients about specific future uses of profits derived from commercialization of research data can ensure both transparency and participation in future primary and secondary precision health research programs.